Foundations of social entrepreneurship : theory, practical tools and skills - Collavo, Tanja, 1988- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Foundations of Social Entrepreneurship presents definitions of social entrepreneurship, explains the benefits and challenges of social entrepreneurs and enterprises, describes the components of an ecosystem of support and presents practical tools to approach social entrepreneurial projects. It is designed to be easily approachable by anyone without prior in-depth knowledge of the subject. The book is divided into two parts; the first provides readers with theoretical foundations to understand the phenomenon of social entrepreneurship, its different interpretations, the context in which it developed and its socio-economic function. The second part of the book covers what it takes to create and manage a social entrepreneurial initiative. Pedagogical features are incorporated throughout to aid learning, including summary tables, international case studies of social entrepreneurs from both developed and emerging economies, as well as suggested exercises and examples of how the tools presented are used in practice. Truly global in its scope, with a strong emphasis on combining theory with practice, this text should be core reading for advanced undergraduate and postgraduate students studying Social Entrepreneurship, Enterprise and Responsible Business. Online resources include chapter-by-chapter PowerPoint slides and instructor's manual"--
Keywords: Social entrepreneurship; Social values -- Economic aspects; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / New Business Enterprises; BUSINESS & ECONOMICS / Development / Sustainable Development